Gonad morphogenesis defects drive hybrid male sterility in asymmetric hybrid breakdown of Caenorhabditis nematodes. Issue 6 (8th September 2014) - Dey, Alivia; Jin, Qi; Chen, Yen‐Chu; Cutter, Asher D.
SUMMARY Determining the causes and evolution of reproductive barriers to gene flow between populations, speciation, is the key to understanding the origin of diversity in nature. Many species manifest hybrid breakdown when they intercross, characterized by increasingly exacerbated problems in later generations of hybrids. Recently, Caenorhabditis nematodes have emerged as a genetic model for studying speciation, and here we investigate the nature and causes of hybrid breakdown between Caenorhabditis remanei and C. latens. We quantify partial F1 hybrid inviability and extensive F2 hybrid inviability; the ∼75% F2 embryonic arrest occurs primarily during gastrulation or embryonic elongation. Moreover, F1 hybrid males exhibit Haldane's rule asymmetrically for both sterility and inviability, being strongest when C. remanei serves as maternal parent. We show that the mechanism by which sterile hybrid males are incapable of transferring sperm or a copulatory plug involves defective gonad morphogenesis, which we hypothesize results from linker cell defects in migration and/or cell death during development. This first documented case of partial hybrid male sterility in Caenorhabditis follows expectations of Darwin's corollary to Haldane's rule for asymmetric male fitness, providing a powerful foundation for molecular dissection of intrinsic reproductive barriers and divergence of genetic pathways controlling organ morphogenesis.